Frederick Luis Aldama. Latinx Superheroes in Mainstream Comics. Tucson: U of Arizona P, 2017. - Danielle A Orozco (Studies in 20th & 21st Century Literature, 2017)
Review of Frederick Luis Aldama. Latinx Superheroes in Mainstream Comics. Tucson: Uof Arizona P, 2017.
Keywords: Latino; Latina; superheroes; comics; animation; film; television; history